2016
DOI: 10.1186/s12863-016-0413-2
|View full text |Cite
|
Sign up to set email alerts
|

Introgression of null allele of Kunitz trypsin inhibitor through marker-assisted backcross breeding in soybean (Glycine max L. Merr.)

Abstract: BackgroundPresence of Kunitz trypsin inhibitor (KTI) in soybean seeds necessitates pre-heat treatment of the soy-flour for its inactivation before using it in food and feed products. The heat treatment not only enhances processing costs of the soy-based foods and feeds but also affects seed-protein quality and solubility. Genetic elimination of KTI is an important and effective approach. Therefore, molecular marker-assisted backcross breeding (MABB) approach was adopted for genetic elimination of KTI from two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 40 publications
1
18
0
1
Order By: Relevance
“…Finally, segregants with ti3/ti3 genotypes were successfully verified for low KTI content and propagated for further yield analysis and development of prospective breeding lines. Our results were similar to those published earlier on the introgression of the null-allele ti3 and MAS to select recombinant genotypes with low KTI content in an Indian soybean breeding program [16,17]. Hybridization and transference of the beneficial ti3 null-alleles determining low KTI in seeds using MAS is very important to enhance the market value and overall soybean seed quality in Kazakhstan.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Finally, segregants with ti3/ti3 genotypes were successfully verified for low KTI content and propagated for further yield analysis and development of prospective breeding lines. Our results were similar to those published earlier on the introgression of the null-allele ti3 and MAS to select recombinant genotypes with low KTI content in an Indian soybean breeding program [16,17]. Hybridization and transference of the beneficial ti3 null-alleles determining low KTI in seeds using MAS is very important to enhance the market value and overall soybean seed quality in Kazakhstan.…”
Section: Discussionsupporting
confidence: 88%
“…The introgression of the ti null-allele at BC 2 F 2 and BC 3 F 2 generations was controlled by Marker-assisted selection (MAS) with ti allele-specific primers and linked SSR markers. Nine and six breeding lines with genetic backgrounds of JS97-52 and DS9712 / DS9814 recurrent parents, respectively, were obtained in Indian breeding programs [16,17]. The introgressed null-allele ti was confirmed in the breeding lines and the KTI content was reduced by 69-84% [16] and an additional seed yield improvement was reported [17].…”
Section: Introductionmentioning
confidence: 92%
“…The Kunitz null trait has been introgressed into different genetic backgrounds and has been utilized to develop soybean cultivars with reduced trypsin inhibitor activity (e.g. BERNARD and HYMOWITZ 1986;BERNARD et al, 1991;VOLLMANN et al, 2003;ALVES DE MORAES et al, 2006;RANI et al, 2011;PERIC et al, 2014;MARANNA et al, 2016; HERMAN and SCHMIDT, 2016; TALUKDAR and SHIVAKUMAR, 2016). In Serbia, for example, Kunitz null soybean cultivars Lana and Laura have been developed for easier livestock feeding and more economical food processing (PERIC et al, 2014).…”
Section: Protease Inhibitorsmentioning
confidence: 99%
“…chromosome 9) and gene specific primers are available now for assisting in the introgression of that trait (e.g. ALVES DE MORAES et al, 2006;KIM et al, 2006;RANI et al, 2011;KUMAR et al, 2013;KUMAR et al, 2015;MARANNA et al, 2016).…”
Section: Protease Inhibitorsmentioning
confidence: 99%
“…The two SSR markers linked with SCN resistance rhg1 locus were further validated by Silva et al (2007) and found that only a combination of two markers provide selection efficiency of 100%. Shivakumar et al (2016) employed MABC for conversion of two high Kunitz trypsin inhibitor (KTI) content soybean varieties (DS 9712 and DS 9814) into low KTI soybean genotypes using three SSR markers. Rosso et al (2011) has developed breeder friendly markers for D-myo-inositol 3-phosphate synthase 1 gene ( MIPS1 ) which causes modifications to seed phosphorus and carbohydrate content in soybean.…”
Section: Prospectus Of Translational Genomics and Breeding In Soybeanmentioning
confidence: 99%